2005
DOI: 10.1016/s0002-9440(10)62350-4
|View full text |Cite
|
Sign up to set email alerts
|

In Response to Protein Load Podocytes Reorganize Cytoskeleton and Modulate Endothelin-1 Gene

Abstract: Effacement of podocyte foot processes occurs in many proteinuric nephropathies and is accompanied by rearrangement of the actin cytoskeleton. Here, we studied whether protein overload affects intracellular pathways, leading to cytoskeletal architecture changes and ultimately to podocyte dysfunction. Mouse podocytes bound and endocytosed both albumin and IgG via receptor-specific mechanisms. Protein overload caused redistribution of F-actin fibers instrumental to up-regulation of the prepro-endothelin (ET)-1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 57 publications
7
136
1
Order By: Relevance
“…In contrast to recent studies suggesting that RhoA maintains F-actin stress fibers of podocytes, [142][143][144] Rac-1 seems to orchestrate an adaptive cellular response to physiological stress or injurious stimuli in AT1R signaling, especially in the F-actin cytoskeleton modulating mechanism. As Rac-1 controls Ang II signaling in podocytes, Rac-1 inhibitors may be thus a potential therapeutic target for protecting podocytes from excess ROS generation and cytoskeletal rearrangement.…”
Section: Rac-1 Orchestrates At1r Signaling On Podocyte Cytoskeletons mentioning
confidence: 60%
“…In contrast to recent studies suggesting that RhoA maintains F-actin stress fibers of podocytes, [142][143][144] Rac-1 seems to orchestrate an adaptive cellular response to physiological stress or injurious stimuli in AT1R signaling, especially in the F-actin cytoskeleton modulating mechanism. As Rac-1 controls Ang II signaling in podocytes, Rac-1 inhibitors may be thus a potential therapeutic target for protecting podocytes from excess ROS generation and cytoskeletal rearrangement.…”
Section: Rac-1 Orchestrates At1r Signaling On Podocyte Cytoskeletons mentioning
confidence: 60%
“…NF-kB promotes Snail transcription 41 and DNA-binding activity of NF-kB is stimulated in cultured podocytes under conditions of increased protein load. 42 It is plausible that both the activation of NF-kB and the inactivation of GSK3b are essential for the accumulation of Snail in podocytes. Snail protein product is also stabilized by p21-activated kinase 1 (PAK1) and by a zinc-finger transporter, LIV1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%